Assessment of mungbean genotypes for durable resistance to Yellow Mosaic Disease: Genotype × Environment interactions. (4th January 2017) - Parihar, Ashok K.; Basandrai, Ashwani K.; Sirari, Asmita; Dinakaran, Dakshinamurthy; Singh, Deepak; Kannan, Kamala; Kushawaha, Kailash P. S.; Adinarayan, Maddineni; Akram, Mohammad; Latha, Tnpalayam Krshnaswamy S.; Paranidharan, Vaikuntavasan; Gupta, Sanjeev
Abstract: Yellow mosaic disease (YMD) is the major constraint of mungbean for realizing high productivity worldwide. Moreover, management of disease using YMD‐resistant genotypes is the simplest approach. Therefore, based on a preliminary screening of 220 genotypes during the year 2010 and 2011 at 17 locations, a set of 25 genotypes was further selected to evaluate at six locations over 2 years for identification of more stable resistant genotypes. The genotype and genotype × environment (GGE) analysis indicated that the genotypes and environment effects were significant (P < 0.001) for YMD incidence. Interestingly, the GGE biplot analysis successfully accounted for 74.71 per cent of the total variation with three genotypes (ML 818, ML 1349 and IPM 02‐14) showing high degree of resistance and stability over the locations. Notably, a strong positive association was observed between disease reaction and temperature, relative humidity and rainfall. As crop is grown in diverse growing environments, aforementioned genotypes can be used as stable/durable sources for future breeding programme to develop YMD‐resistant cultivars.